Measuring the baryonic Tully-Fisher relation below the detection threshold - Pan, H; Jarvis, MJ; Ponomareva, AA; Santos, MG; Allison, JR; Maddox, N; Frank, BS (Oxford University Press, 2021)
We present a novel 2D flux density model for observed H i emission lines combined with a Bayesian stacking technique to measure the baryonic Tully-Fisher relation below the nominal detection threshold. We simulate a galaxy catalogue, which includes H i lines described with either Gaussian or busy function profiles, and H i data cubes with a range of noise and survey areas similar to the MeerKAT International Giga-Hertz Tiered Extragalactic Exploration (MIGHTEE) survey. With prior knowledge of redshifts, stellar masses, and inclinations of spiral galaxies, we find that our model can reconstruct the input baryonic Tully-Fisher parameters (slope and zero-point) most accurately in a relatively broad redshift range from the local Universe to z = 0.3 for all the considered levels of noise and survey areas and up to z = 0.55 for a nominal noise of 90 μJy/channel over 5 deg2. Our model can also determine the MHI - M∗ relation for spiral galaxies beyond the local Universe and account for the detailed shape of the H I emission line, which is crucial for understanding the dynamics of spiral galaxies. Thus, we have developed a Bayesian stacking technique for measuring the baryonic Tully-Fisher relation for galaxies at low stellar and/or H I masses and/or those at high redshift, where the direct detection of H I requires prohibitive exposure times.